Patterns of enrollment to community-based health insurance and the situations influencing utilization of the services in Southern Ethiopia: a qualitative study - Getahun Siraw; Bewunetu Zewude; Muluken Meshesha (Cogent Public Health)
A community-based health insurance (CBHI) scheme was proposed by the World Health Organization, hoping that it would provide financial protection by reducing out-of-pocket expenditure and enhancing health-seeking behavior. The utilization of CBHI, however, is influenced by a variety of factors. Because these factors differ according to differing socio-economic contexts and understanding them in a specific context would help to improve the use of the scheme, we examined the situations influencing the utilization of CBHI in Sodo Zuria woreda, southern Ethiopia. Using a phenomenological approach, the study relied on qualitative data from 21 in-depth interviews and 4 FGDs with beneficiaries, as well as 12 key informant interviews with health professionals and kebele leaders. Audio records were first transcribed verbatim, translated to English, and transported to Atlas.ti 7 software. Transcriptions, along with field notes and memos, were coded, and subsequently, themes and sub-themes were identified. Accordingly, the study revealed that low levels of educational attainment, lack of program awareness, lack of pharmaceuticals and medical supplies, lack of adequate healthcare professionals, distance from home, and administrative complexities undermine the utilization of community-based health insurance. The situation exposes beneficiaries to out-of-pocket medical expenses, thereby negating the goal of the CBHI program. As a result, the Ministry of Health, in conjunction with other governmental and non-governmental bodies, should ensure that enough pharmaceuticals and medical supplies are provided. In addition, efforts should be made to make sure that there are enough health workers and that a convenient working procedure is established in health centers.